Polymer solid electrolyte and lithium secondary battery

By introducing polyols into the polymer matrix and forming a three-dimensional network structure, the problems of low ionic conductivity and poor mechanical properties caused by high crystallinity of polymer solid electrolyte are solved, and the circulation performance and service life of the battery are improved by complexing metal ions.

CN119920974AActive Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411984764.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing polymer solid electrolytes have high crystallinity, low ion conductivity, low lithium ion migration number, and poor mechanical properties, which limit their application. In addition, the lithium battery positive electrode material will cause metal ions to dissolve during charging and discharging, which will reduce the battery cycle life.

Method used

By introducing polyols into the polymer matrix and using polyisocyanate to form a three-dimensional network structure, the crystallinity of the polymer matrix is ​​reduced, the ionic conductivity and the number of lithium ion migration are improved, and the mechanical strength is enhanced. The metal ions dissolved by electrons on the positive electrode are complexed by the lone of N atoms in the polyisocyanate to prevent their deposition.

Benefits of technology

It improves the ion conduction ability of solid electrolytes and its tolerance to dendrites, extends the circulation performance and service life of lithium secondary batteries, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222313980000171
    Figure BDA0005222313980000171
Patent Text Reader

Abstract

The invention provides a polymer solid electrolyte and a lithium secondary battery. The polymer solid electrolyte comprises a modified polymer matrix as a component (A) and a lithium salt as a component (B), wherein the polymer matrix (A1) in the modified polymer matrix as the component (A) comprises a repeating unit with the following structure (1):-R-O-(1), R represents alkylene with a straight chain or branched chain structure with the carbon atom number of 2-5, and O represents an alkyl group with the carbon atom number of 2-5; the modification comprises the formation of a three-dimensional network structure from a polyol as component (A3) with the polymer matrix (A1) by means of a polyisocyanate component as component (A2), and the formation of the three-dimensional network structure is at least partially carried out in the presence of a latent curing agent as component (A4). The polymer solid electrolyte provided by the invention can improve the ionic conductivity, the lithium ion transference number, the mechanical strength of a base material, the cycle performance of a secondary battery and the service life of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer solid electrolyte and a lithium secondary battery, belonging to the technical field of lithium ion batteries. Background Art

[0002] As an efficient energy storage and conversion device, lithium-ion batteries have high energy density and have attracted widespread attention due to their good cycle performance and high reliability. However, commercial lithium batteries currently usually use organic solutions containing various lithium salts as liquid electrolytes. In practical applications, liquid electrolytes have many disadvantages and safety hazards such as poor chemical stability, flammability and explosion risks. The use of solid electrolytes ensures the safety of lithium-ion batteries, which have the advantages of high energy density, good cycle performance, long service life, and wide electrochemical window, making the battery safer, more durable, with higher energy density and simple battery structure design.

[0003] Solid electrolytes mainly include inorganic solid electrolytes and organic polymer solid electrolytes. Among many polymer systems, PEO is considered to be the most ideal polymer substrate. However, PEO solid electrolytes have high crystallinity, which interferes with the movement of polymer segments and lithium ions, resulting in low ion conductivity and low lithium ion transfer number, which limits their practical application.

[0004] In addition, during the charging and discharging process, the positive electrode material of the lithium battery will be accompanied by the dissolution of metal ions (such as Ni, Co, Mn, Fe, Al, etc.) and deposition on the surface of the negative electrode material, reducing the battery cycle life.

[0005] Some documents disclose a PEO solid electrolyte modified with waterborne polyurethane, which is modified by compounding waterborne polyurethane with PEO under the condition of water participation, thereby achieving the purpose of improving ionic conductivity and mechanical properties. However, in the environment of water participation, the isocyanate in the polyurethane may react with water to generate carbon dioxide, thereby destroying the solid electrolyte structure, and there is a concern that the battery cycle stability performance will be reduced, so the problem of battery cycle life is not solved.

[0006] It can be seen that although some research has been conducted on polymer solid electrolytes in this field, there is still room for further improvement in the development of polymer solid electrolytes that have high ionic conductivity, high lithium ion transfer number, mechanical properties, and excellent battery cycle life. Summary of the invention

[0007] Problem that the invention aims to solve

[0008] As mentioned above, PEO-type polymers are used as polymer matrices. Since their main chains contain strong electron-donating groups, they have good ion conductivity. However, they have the problem of easy crystallization. The existence of crystalline regions limits their ion conductivity. In addition, the mechanical properties of PEO itself are not outstanding, and its resistance to dendrites is not strong.

[0009] In addition, although solid electrolytes based on materials such as PEO have advantages such as good safety, the positive electrode material of lithium batteries will be accompanied by the dissolution of metal ions (such as Ni, Co, Mn, Fe, Al, etc.) and deposition on the surface of the negative electrode material during the charging and discharging process, thereby significantly reducing the battery cycle life.

[0010] In order to solve the above problems, the present invention provides a polymer solid electrolyte, which is mainly obtained by (chemical) modification of PEO-based polymer substrates, that is, by introducing polyols into the polymer substrates, and forming a three-dimensional network structure through polyisocyanates and latent curing agents, not only can the crystallinity of the polymer substrates be reduced to improve the ionic conductivity and the number of lithium ion migration, but also the mechanical strength of the substrates can be improved. In addition, a large number of N atoms introduced due to the use of polyisocyanates have lone pairs of electrons, and therefore, can also play an effective complexing role on the metal ions dissolved from the positive electrode of the battery. As a result, the ion conductivity of the solid electrolyte and the tolerance to dendrites are improved, and the cycle performance and service life of the secondary battery are also improved.

[0011] Furthermore, the present invention also provides a lithium secondary battery, wherein the lithium secondary battery comprises the polymer solid electrolyte described above.

[0012] Solutions for solving problems

[0013] The present invention first provides a polymer solid electrolyte, wherein the polymer solid electrolyte comprises a modified polymer matrix as component (A) and a lithium salt as component (B);

[0014] The polymer matrix (A1) in the modified polymer matrix as component (A) comprises repeating units having the following structure (1):

[0015] -RO-(1)

[0016] Wherein, R represents a linear or branched alkylene group having 2 to 5 carbon atoms,

[0017] The modification includes forming a three-dimensional network structure with the polyol as component (A3) and the polymer base (A1) through the polyisocyanate component as component (A2), and the formation of the three-dimensional network structure is at least partially carried out in the presence of a latent curing agent as component (A4).

[0018] According to the polymer solid electrolyte of the present invention, the polymer matrix as component (A1) includes polyethylene oxide.

[0019] According to the polymer solid electrolyte of the present invention, the polyisocyanate component of the component (A2) includes one or more of aliphatic polyisocyanate, alicyclic polyisocyanate and aromatic polyisocyanate.

[0020] According to the polymer solid electrolyte of the present invention, the polyol of the component (A3) comprises a polymer polyol having a hydroxyl group on a side chain.

[0021] According to the polymer solid electrolyte of the present invention, the polyol of component (A3) includes at least one of polyvinyl alcohol (PVA) and ethylene-vinyl alcohol copolymer (EVOH).

[0022] According to the polymer solid electrolyte of the present invention, the latent curing agent as component (A4) can decompose under ambient humidity to generate hydroxyl groups and / or amino groups.

[0023] According to the polymer solid electrolyte of the present invention, in the modified polymer matrix component (A), the molar ratio of the amount derived from component (A3) to the amount derived from the polymer matrix (A1) is 1:4 to 1:12; and / or,

[0024] In the modified polymer matrix component (A), the molar ratio of the amount derived from component (A3) to the amount derived from the polyisocyanate in component (A2) is 1:0.02 to 1:0.44; and / or,

[0025] In the modified polymer matrix component (A), the molar ratio of the amount derived from the component (A3) to the amount derived from the latent curing agent of the component (A4) is 1:0.2 to 1:0.4.

[0026] According to the polymer solid electrolyte of the present invention, the modification is carried out by one of the following methods:

[0027] a. grafting the component (A3) polyol with the polymer base (A1) to obtain a graft, and then completing the formation of the three-dimensional network structure in the presence of the component (A2) polyisocyanate component and the component (A4) latent curing agent;

[0028] b. Pre-reacting the polyol component (A3) with the polyisocyanate component (A2) to obtain a pre-reactant, and then reacting the pre-reactant with the polymer matrix in the presence of the latent curing agent component (A4) to form the three-dimensional network structure.

[0029] According to the solid electrolyte of the present invention, wherein, in the method a, the grafted product obtained by the grafting reaction is a comb-shaped grafted product with the molecular weight of the polymer matrix as the side chain; and in the method b, it includes coating the pre-reactant on the polymer matrix or blending the pre-reactant with the polymer matrix.

[0030] Furthermore, the present invention also provides a lithium secondary battery, wherein the lithium secondary battery includes or uses the polymer solid electrolyte according to the present invention, and preferably, the lithium secondary battery is an all-solid electrolyte lithium secondary battery.

[0031] Effects of the Invention

[0032] 1) The polymer solid electrolyte provided by the present invention introduces a polyol substance, and with the help of polyisocyanate, the polyol and the polymer matrix form a three-dimensional network structure, thereby inhibiting the formation of a crystalline region of the polymer matrix, reducing the crystallinity of the polymer matrix, enhancing the movement of chain segments and lithium ions, and improving the ion conductivity and lithium ion transfer number of the polymer solid electrolyte; at the same time, the three-dimensional network structure formed improves the mechanical strength of the polymer solid electrolyte, improves the tolerance of the polymer solid electrolyte to lithium dendrites, and improves the safety performance of the battery.

[0033] 2) The lone pair electrons of the N atom in the polyisocyanate in the modified polymer matrix and the polyol substances can complex the multivalent metal ions dissolved from the positive electrode, hinder the deposition of the dissolved ions at the negative electrode, and improve the cycle performance and cycle life of the battery.

[0034] 3) The three-dimensional network structure is finally formed in the presence of a latent curing agent, thereby preventing the polyisocyanate from reacting with water to produce carbon dioxide, preventing the structure of the polymer solid electrolyte from being destroyed, eliminating the influence of moisture in the battery on the solid electrolyte, improving the structural stability of the polymer solid electrolyte, and further improving the ionic conductivity of the polymer solid electrolyte and the cycle performance of the battery.

[0035] 4) In some specific embodiments, the modified polymer matrix further comprises aromatic groups (eg, aromatic isocyanate), which further improves the mechanical strength of the polymer solid electrolyte. DETAILED DESCRIPTION

[0036] The following is a detailed description of the present invention. The following description of the technical features is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0037] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0038] In this specification, the numerical range expressed using "above" or "below" means a numerical range including the number.

[0039] In this specification, the word "may" includes both performing a certain process and not performing a certain process.

[0040] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0041] In this specification, the term "normal temperature" or "room temperature" refers to an indoor ambient temperature of "23±2°C".

[0042] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.

[0043] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model, theoretical data or target data is within a numerical range of 1%, preferably 0.8%, and more preferably 0.5%.

[0044] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.

[0045] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0046] The present invention mainly provides a polymer solid electrolyte, which can improve the mechanical strength, cycle stability and cycle life of the battery while improving the ionic conductivity and lithium ion migration number of the polymer solid electrolyte by introducing a polyol component into a traditional polymer matrix and forming a three-dimensional network structure via polyisocyanate.

[0047] The present invention is mainly obtained through the following insights:

[0048] In order to solve the problem of low ion conductivity caused by high crystallinity of traditional PEO-based polymer solid electrolytes at room temperature, the present invention attempts to modify them using polyols and polyisocyanates so that the polymer matrix and the polyols form a three-dimensional network structure through the polyisocyanate.

[0049] The formation of this structure reduces the original crystallization of the PEO polymer matrix, thereby improving its ion transmission capacity. On the other hand, the three-dimensional network structure can significantly improve the mechanical properties of the polymer matrix, especially its ability to prevent dendrite puncture, thereby improving the life and safety of the battery.

[0050] In addition, by introducing a certain amount of polyisocyanate, N atoms with lone pairs of electrons can also be introduced. The N atoms and polyols can complex high-valent metal ions, especially transition metal ions, thereby preventing transition metal ions (such as Ni, Co, Mn, Fe, Al, etc.) dissolved from the positive electrode from being deposited on the surface of the negative electrode material.

[0051] <First aspect>

[0052] A first aspect of the present invention provides a polymer solid electrolyte, the polymer solid electrolyte comprising a modified polymer matrix as component (A), and a lithium salt as component (B);

[0053] The polymer matrix (A1) in the modified polymer matrix as component (A) comprises repeating units having the following structure (1):

[0054] -RO-(1)

[0055] Wherein, R represents a linear or branched alkylene group having 2 to 5 carbon atoms,

[0056] The modification includes forming a three-dimensional network structure with the polyol as component (A3) and the polymer base (A1) through the polyisocyanate component as component (A2), and the formation of the three-dimensional network structure is at least partially carried out in the presence of a latent curing agent as component (A4).

[0057] (Component (A))

[0058] The modified polymer matrix as component (A) described in the present invention is obtained by (chemically) modifying the polymer matrix (A1) with polyisocyanate (A2) and polyol (A3). The three-dimensional network structure formed by the three improves the electrical and mechanical properties of the polymer matrix and at the same time gives it good transition metal capture ability.

[0059] Component (A1)

[0060] The polymer base (A1) to be modified in the present invention mainly includes polymers having repeating units of the above structure (1).

[0061] In some specific embodiments of the present invention, the R can be an ethylene, propylene or isopropylene structure, and more preferably the R can be an ethylene, that is, preferably, the polymer matrix (A1) of the present invention mainly includes polyethylene oxide or is substantially formed thereof.

[0062] In principle, there is no particular limitation on the molecular weight or glass transition temperature of the component (A1), and the component (A1) can be configured according to the existing principles of solid electrolytes.

[0063] Component (A2)

[0064] The polyisocyanate of the component (A2) of the present invention is mainly used to allow the component (A1) and the polyol of the component (A3) described below to form a three-dimensional network structure.

[0065] In principle, the polyisocyanate that can be used in the present invention is not particularly limited, and can be selected from one or more of aliphatic polyisocyanates, alicyclic polyisocyanates, or aromatic polyisocyanates.

[0066] The number of isocyanate groups in the polyisocyanate may generally be 2 or more, preferably 2 to 6, and in some preferred embodiments, the isocyanate groups are at least partially or entirely located at the ends of the polyisocyanate structure.

[0067] The aliphatic polyisocyanate is not particularly limited and includes linear or branched aliphatic polyisocyanates, and examples thereof include hexamethylene diisocyanate and trimethylhexamethylene diisocyanate.

[0068] The alicyclic polyisocyanate is not particularly limited, and examples thereof include isophorone diisocyanate.

[0069] The aromatic polyisocyanate is not particularly limited, and examples thereof include toluene diisocyanate, 4,4'-diphenylmethane diisocyanate (hereinafter sometimes abbreviated as "MDI"), xylylene diisocyanate, naphthalene diisocyanate, triphenylmethane-4,4',4"-triisocyanate, 1,3,5-triisocyanatobenzene, 2,4,6-triisocyanatotoluene, and 4,4'-dimethyldiphenylmethane-2,2',5,5'-tetraisocyanate.

[0070] In addition, in addition to the above-mentioned polyisocyanates as monomer compounds, the polyisocyanates of the present invention may also be prepolymers having isocyanate groups at the ends, for example, these prepolymers may be obtained by prepolymerization of isocyanate monomers and polyol compounds. Such polyol compounds are not particularly limited in principle and may include aliphatic linear or branched polyols, alicyclic polyols, aromatic polyols, polyester polyols, polyurethane polyols, polyether polyols, and the like.

[0071] In a further preferred embodiment of the present invention, from the perspective of improving the mechanical strength of the final polymer solid electrolyte, aromatic polyisocyanates can be used in the polyisocyanate of component (A2) of the present invention. There is no particular limitation on the content of aromatic polyisocyanates in the polyisocyanate of component (A2) in principle, for example, it can be 50% by mass or less, preferably 10 to 30% by mass.

[0072] Component (A3)

[0073] The polyol of component (A3) of the present invention generally has 3 or more, preferably 5 or more, and more preferably 10 or more hydroxyl groups per molecule.

[0074] In some preferred embodiments of the present invention, such polyol may be a polymer polyol having hydroxyl groups on the side chains.

[0075] From the perspective of improving the crystallinity of component (A1), such polyols may be one or more of polyvinyl alcohol (PVA) and ethylene-vinyl alcohol (EVOH). More preferably, component (A3) of the present invention may be polyvinyl alcohol. In addition, there is no particular limitation on the saponification degree of polyvinyl alcohol in principle, and it may generally be 80% or more, preferably 90% or more, and more preferably 98% or more.

[0076] Furthermore, the molecular weight of the polyol can generally be 500 Da to 200 million Da, for example, it can be 1500 Da, 2000 Da, 5000 Da, 10000 Da, 10000 Da, 200000 Da, 500000 Da, 800000 Da, 1 million Da, 2 million Da, 3 million Da, 5 million Da, 10 million Da, 20 million Da, 50 million Da, 100 million Da, 150 million Da, etc.

[0077] Component (A4)

[0078] The component (A4) of the present invention is a latent curing agent, which can release active hydrogen groups in the presence of water.

[0079] In some specific embodiments of the present invention, the latent curing agent can react with moisture in the air at room temperature and normal humidity to release active hydrogen groups.

[0080] Furthermore, in some specific embodiments of the present invention, the active hydrogen may be one or both of an amino group and a hydroxyl group.

[0081] In some more specific embodiments, the latent curing agent can be listed as a combination of one or more of imine latent curing agents, oxazolidine latent curing agents, etc., wherein the imine latent curing agent can include one or more of triethylenediamine, polyethyleneimine, polycarbodiimide, etc.

[0082] The latent curing agent of the present invention can prevent the isocyanate group from reacting with the residual water in the system or the water in the atmosphere to generate carbon dioxide and cause bubbles, thereby improving the quality of the cross-linked product.

[0083] Other Ingredients

[0084] In principle, there are no particular limitations on other components that can be used to form component (A). For example, various polyurethane-forming catalysts may be used, if necessary, to promote the reaction of components (A2) and (A3).

[0085] Dosage of each component

[0086] The amount of each component used in forming component (A) can be adjusted in principle according to the characteristics of component (A1).

[0087] In some preferred embodiments of the present invention, from the perspective of improving crystallization resistance, mechanical properties, and the ability to capture transition metal ions:

[0088] The molar ratio of the component (A3) to the component (A1) can be 1:4 to 1:12, for example, 1:6, 1:7, 1:8, 1:9, etc. When the molar ratio of the component (A3) polyol to the component (A1) polymer matrix is ​​1:4 to 1:12, on the one hand, the component (A3) polyol can better reduce the crystallinity of the component (A1) polymer matrix and improve the ionic conductivity; on the other hand, the component (A3) polyol can effectively complex the multivalent metal ions dissolved from the positive electrode, hinder the dissolved metal ions from depositing at the negative electrode, and improve the cycle life of the battery.

[0089] The molar ratio of the component (A3) to the component (A2) can be 1:0.02 to 1:0.44, for example, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, etc. When the molar ratio of the component (A3) polyol to the component (A2) polyisocyanate is 1:0.02 to 1:0.44, it can better form a three-dimensional network with the component (A1) polymer matrix, reduce the crystallinity of the polymer matrix, improve the ionic conductivity and the lithium ion transfer number while improving the mechanical strength.

[0090] The molar ratio of the component (A3) to the component (A4) can be 1:0.2 to 1:0.4, for example, 1:0.22, 1:0.25, 1:0.28, 1:0.3, 1:0.32, 1:0.35, 1:0.38, etc. When the molar ratio of the component (A3) polyol to the component (A4) latent curing agent is 1:0.2 to 1:0.4, it can prevent the carbon dioxide generated by the reaction of polyisocyanate and water during the polymerization of the polyurethane compound from destroying the structure of the solid electrolyte, thereby improving the structural stability of the polymer solid electrolyte and further improving the ionic conductivity and the cycle stability of the battery.

[0091] (Component (B))

[0092] The lithium salt as component (B) described in the present invention is the source of active ions in the polymer solid electrolyte and is itself included in the polymer solid electrolyte system. Without the lithium salt, the polymer solid electrolyte will lose the function of conducting active ions and the entire battery will not work.

[0093] Regarding the type of lithium salt, in some specific embodiments of the present invention, the lithium salt can be selected from one or more salts formed by lithium ions and the following anions: PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、N(FSO2)2 - 、C(CF2SO2)3 - 、C2BF2O4 - Preferably, the lithium salt may be lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0094] (Other components)

[0095] The polymer solid electrolyte of the present invention may optionally include other components in addition to the above-mentioned components (A) and (B).

[0096] For example, in some specific embodiments, in addition to component (A), other polymer matrices may be used in the solid electrolyte.

[0097] In principle, there is no particular restriction on the types of these other polymer matrices, and they can be selected from one or more combinations of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer (PVDF-TrFE-CTFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyurethane (PU), polyurea (PUA), etc.

[0098] Furthermore, based on the total mass of the polymer matrix, the content of these other polymer matrixes may be 10 mass % or less, for example, 8 mass % or less, 5 mass % or less, etc.

[0099] The (usage) form of polymer solid electrolyte

[0100] Regarding the form of the polymer solid electrolyte of the present invention, in some specific embodiments, the above-mentioned polymer solid electrolyte composition can be provided separately, and such a composition can be used to prepare a film-forming material.

[0101] In addition, the solid electrolyte of the present invention is essentially a fully solid electrolyte, that is, it does not substantially contain a solvent or a liquid electrolyte.

[0102] <Second Aspect>

[0103] The second aspect of the present invention provides a method for preparing the polymer solid electrolyte described in the first aspect.

[0104] In general, the polymer solid electrolyte of the present invention can be obtained by mixing component (A) and component (B) in any form.

[0105] The preparation of component (A) can preferably be carried out by one of the following methods:

[0106] a. grafting the component (A3) polyol with the polymer base (A1) to obtain a graft, and then completing the formation of the three-dimensional network structure in the presence of the component (A2) polyisocyanate component and the component (A4) latent curing agent;

[0107] b. Pre-reacting the polyol component (A3) with the polyisocyanate component (A2) to obtain a pre-reactant, and then reacting the pre-reactant with the polymer base (A1) in the presence of a latent curing agent component (A4) to form the three-dimensional network structure.

[0108] Specifically:

[0109] Method a

[0110] In this route, a grafted product is first prepared. For the grafted product, component (A1) can be grafted onto component (A3) via methods such as anionic or cationic initiators.

[0111] In some preferred embodiments of the present invention, the above-mentioned graft can be a comb-shaped graft, in which the component (A1) is grafted to the hydroxyl groups on the side chains of the component (A3) to form a comb-shaped graft with the molecular chains of the component (A1) as side chains.

[0112] The end of the graft still retains a hydroxyl group, therefore, the graft is further reacted with component (A2) polyisocyanate in the presence of (A4) latent curing agent. For the reaction, it is usually controlled to be carried out under anhydrous and oxygen-free conditions, and optionally, various organic solvents can be used. For the type of organic solvent, it is not particularly limited and can be selected as needed, for example, one or more of acetonitrile, anisole, chloroform, dichloroethane and dimethylformamide can be included. And, in the reaction, polyisocyanate can at least partially form a three-dimensional network structure between the above-mentioned (side chain) grafts. When the obtained component (A1) is exposed to the atmosphere, due to the presence of moisture in the atmosphere, the latent curing agent is further decomposed to produce active hydrogen to complete the final three-dimensional network structure.

[0113] In addition, the above-mentioned grafted product can be obtained through the above-mentioned grafting reaction or can be obtained commercially. For example, PVA-g-PEO can be obtained commercially.

[0114] Method b

[0115] In this route, the (A3) polyol and the component (A2) polyisocyanate component can be pre-reacted to obtain a pre-reactant, and such a pre-reactant can have at least a partial three-dimensional network structure. The pre-reaction can be optionally carried out in the presence of an organic solvent. The amount of the organic solvent is not particularly limited in the present invention, as long as the reactant can be fully dissolved. In some specific embodiments, the concentration of the component (A3) polyol in the pre-reaction solution is 40 g / L or less, for example 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, etc.

[0116] In addition, the above reaction can also be carried out in the presence of a latent curing agent as component (A4), because the reaction is controlled to be oxygen-free and water-free, and component (A4) does not substantially participate in the reaction. Further, the pre-reactant is contacted with component (A1), and finally, when exposed to air, under the action of the latent curing agent, the pre-reactant and component (A1) complete the final three-dimensional network structure.

[0117] In principle, there is no particular limitation on the contacting, and the pre-reactant may be coated on the polymer matrix or blended with the polymer matrix. Coating here also includes allowing the pre-reactant to penetrate into the polymer matrix.

[0118] Further, after obtaining the above-mentioned component (A), it can be mixed with the lithium salt of component (B) to obtain the final solid electrolyte. In some preferred embodiments, the latent curing agent of component (A4) in the component (A) can be added after the components (A1), (A2), (A3) and (B) are mixed to obtain the final solid electrolyte.

[0119] The final solid electrolyte may be processed before packaging in an optional manner.

[0120] In some specific embodiments, the preparation method further includes the step of forming a film of the solid electrolyte. The film forming method may be a solution coating method, an extrusion casting method or the like.

[0121] In some more specific embodiments, the solution coating method includes applying the solution to a substrate and drying it, removing the substrate, thereby obtaining a film-like polymer solid electrolyte. There is no particular limitation on the substrate, for example, it can be a glass substrate, a ceramic substrate, a stainless steel substrate, a plastic substrate, etc. For the drying temperature and time, for example, it can be dried in a vacuum drying oven at 50 to 100°C, preferably 60 to 80°C for 4 to 10 hours, preferably 4 to 8 hours. After drying, a thin film on the substrate can be obtained. Peeling the film off the substrate (i.e., removing the substrate) can obtain a film-like polymer solid electrolyte. In addition, the obtained film-like polymer solid electrolyte can also be cut into a suitable shape and size as needed, for example, it can be cut into a circular electrolyte sheet of Φ16mm.

[0122] The preparation method of the present invention has many advantages such as low cost, simple method, environmental friendliness, and high safety of the prepared polymer solid electrolyte, and has extremely broad prospects in practical application.

[0123] <Third Aspect>

[0124] The fourth aspect of the present invention provides a lithium secondary battery, in particular a lithium secondary battery comprising or using the polymer solid electrolyte of the first aspect of the present invention or a polymer solid electrolyte prepared according to the preparation method of the second aspect.

[0125] Such a secondary battery includes at least a positive electrode, a negative electrode, and a solid electrolyte.

[0126] In addition, the positive electrode in the battery may be a lithium oxide doped with a common transition metal, specifically, a lithium oxide doped with a transition metal such as Mn, Co, Al, Fe and Ni; preferably, the positive electrode may be an NCM or NCA positive electrode.

[0127] There is no particular limitation on the negative electrode, which may be a common negative electrode for solid polymer batteries. Preferably, the negative electrode is a lithium negative electrode.

[0128] Example

[0129] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0130] Example 1

[0131] The purchased PVA-g-PEO (the molar ratio of PVA to PEO is 1:10), toluene diisocyanate and lithium bis(fluorosulfonyl)imide (LiFSI) are dissolved in dimethylformamide, and then triethylenediamine is added to obtain a mixed solution, wherein the molar ratio of PVA-g-PEO (based on PVA as a structural unit), toluene diisocyanate and triethylenediamine in the mixed solution is 1:0.02:0.2, wherein the concentration of PVA is 20 g / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 10%, and the mixed solution is heated to react under anhydrous and oxygen-free conditions to obtain a polymer solid electrolyte membrane.

[0132] Example 2

[0133] The purchased PVA-g-PEO (the molar ratio of PVA to PEO is 1:10), toluene diisocyanate and lithium bis(fluorosulfonyl)imide (LiFSI) are dissolved in dimethylformamide, and then triethylenediamine is added to obtain a mixed solution, wherein the molar ratio of PVA-g-PEO (based on PVA as a structural unit), toluene diisocyanate and triethylenediamine in the mixed solution is 1:0.044:0.2, wherein the concentration of PVA is 20 g / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 10%, and the mixed solution is heated to react under anhydrous and oxygen-free conditions to obtain a polymer solid electrolyte membrane.

[0134] Example 3

[0135] The purchased PVA-g-PEO (the molar ratio of PVA to PEO is 1:10), toluene diisocyanate and lithium bis(fluorosulfonyl)imide (LiFSI) are dissolved in dimethylformamide, and then triethylenediamine is added to obtain a mixed solution, wherein the molar ratio of PVA-g-PEO (based on PVA as a structural unit), toluene diisocyanate and triethylenediamine in the mixed solution is 1:0.02:0.4, wherein the concentration of PVA is 20 g / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 10%, and the mixed solution is heated to react under anhydrous and oxygen-free conditions to obtain a polymer solid electrolyte membrane.

[0136] Example 4

[0137] The purchased PVA (the molar ratio of PVA to PEO is 1:10), toluene diisocyanate and lithium bis(fluorosulfonyl)imide (LiFSI) are dissolved in dimethylformamide, and then triethylenediamine is added to obtain a mixed solution, wherein the molar ratio of PVA (calculated as PVA as a structural unit), toluene diisocyanate and triethylenediamine in the mixed solution is 1:0.44:0.4, wherein the concentration of PVA is 20 g / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 10%, the mixed solution is heated to react under anhydrous and oxygen-free conditions, and applied to the negative electrode side of the PEO solid electrolyte to obtain a polymer solid electrolyte membrane.

[0138] Example 5

[0139] The purchased PVA (the molar ratio of PVA to PEO is 1:10), toluene diisocyanate and lithium bis(fluorosulfonyl)imide (LiFSI) are dissolved in dimethylformamide, and then triethylenediamine is added to obtain a mixed solution, wherein the molar ratio of PVA (calculated as PVA as a structural unit), toluene diisocyanate and triethylenediamine in the mixed solution is 1:0.1:0.2, wherein the concentration of PVA is 20 g / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 10%, the mixed solution is heated to react under anhydrous and oxygen-free conditions, and then directly blended with PEO solid electrolyte to obtain a polymer solid electrolyte membrane.

[0140] Example 6

[0141] The purchased PVA-g-PEO (PVA to PEO molar ratio of 1:5), toluene diisocyanate and lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in dimethylformamide, and then triethylenediamine was added to obtain a mixed solution, wherein the molar ratio of PVA-g-PEO (based on PVA as a structural unit), toluene diisocyanate and triethylenediamine in the mixed solution was 1:0.02:0.2, wherein the concentration of PVA was 20 g / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) was 10%, and the mixed solution was heated to react under anhydrous and oxygen-free conditions to obtain a polymer solid electrolyte membrane.

[0142] Example 7

[0143] The difference from Example 1 is that toluene diisocyanate is replaced by diphenylmethane diisocyanate (MDI).

[0144] Comparative Example 1

[0145] The purchased PVA-g-PEO (the molar ratio of PVA to PEO is 1:10), toluene diisocyanate and lithium bis(fluorosulfonyl)imide (LiFSI) are dissolved in dimethylformamide to obtain a mixed solution, wherein the molar ratio of PVA-g-PEO (based on PVA as a structural unit) to toluene diisocyanate in the mixed solution is 1:0.044, wherein the concentration of PVA is 20 g / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 10%, and the mixed solution is heated to react under anhydrous and oxygen-free conditions to obtain a polymer solid electrolyte membrane.

[0146] Comparative Example 2

[0147] The purchased PVA-g-PEO (PVA to PEO molar ratio 1:10) was directly used as the solid electrolyte.

[0148] Comparative Example 3

[0149] The difference from Example 1 is that no triethylenediamine is used.

[0150] Performance Testing

[0151] 1. Ionic conductivity

[0152] The ionic conductivity of the polymer solid electrolyte membranes in the embodiment and the comparative example was measured by a four-electrode method. The test results are shown in Table 1.

[0153] 2. Ion transfer number

[0154] The polymer solid electrolyte membranes in the embodiments and comparative examples were assembled into CR2032 type Li|electrolyte|Li symmetric button cells, and then the electrochemical impedance spectroscopy (EIS) and DC polarization tests were measured by constant potential chronoamperometry to obtain the ion transfer number. The test results are shown in Table 1.

[0155] 3. Battery cycle performance

[0156] The polymer solid electrolyte membranes in the embodiments and comparative examples were assembled into CR2032 button NCM811 positive electrode | electrolyte | Li battery, and the cycle stability was tested at a current density of 0.33C / 0.33C. The test termination condition was 80% SOH. The test results are shown in Table 1.

[0157] Table 1 Performance test results of embodiments and comparative examples

[0158]

[0159] As shown in Table 1, it can be seen from the comparison between Examples 1 to 7 and Comparative Example 2 that by adjusting the ratio between the polymer matrix and the polyol and introducing an appropriate amount of diisocyanate and latent curing agent, the ion transport performance and cycle performance of the solid electrolyte can be effectively improved, thereby improving the electrochemical performance and service life of the solid-state battery.

[0160] From the comparison of Comparative Examples 1 and 3 with Comparative Example 2, it can be seen that although the introduction of diisocyanate into PVA-g-PEO alone can improve the ion transport performance and cycle performance of the solid electrolyte to a certain extent, the degree of improvement is limited. By further introducing a latent curing agent (Example 1), the ionic conductivity of the polymer solid electrolyte and the cycle performance of the battery can be further significantly improved.

[0161] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0162] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A polymer solid electrolyte, characterized in that: The polymer solid electrolyte comprises a modified polymer matrix as component (A) and a lithium salt as component (B); The polymer matrix (A1) in the modified polymer matrix as component (A) comprises repeating units having the following structure (1): -RO-(1) Wherein, R represents a linear or branched alkylene group having 2 to 5 carbon atoms, The modification includes forming a three-dimensional network structure with the polyol as component (A3) and the polymer base (A1) through the polyisocyanate component as component (A2), and the formation of the three-dimensional network structure is at least partially carried out in the presence of a latent curing agent as component (A4).

2. The polymer solid electrolyte according to claim 1, characterized in that The polymer matrix as component (A1) includes polyethylene oxide.

3. The polymer solid electrolyte according to claim 1 or 2, characterized in that: The polyisocyanate component of the component (A2) includes one or more of aliphatic polyisocyanate, alicyclic polyisocyanate and aromatic polyisocyanate.

4. The polymer solid electrolyte according to any one of claims 1 to 3, characterized in that: The polyol of the component (A3) includes a polymer polyol having a hydroxyl group in a side chain.

5. The polymer solid electrolyte according to claim 4, characterized in that: The polyol of the component (A3) includes at least one of polyvinyl alcohol and ethylene-vinyl alcohol copolymer.

6. The polymer solid electrolyte according to any one of claims 1 to 5, characterized in that: The latent curing agent of component (A4) can decompose under ambient humidity to generate hydroxyl groups and / or amino groups.

7. The polymer solid electrolyte according to any one of claims 1 to 6, characterized in that: In the modified polymer matrix component (A), the molar ratio of the amount derived from the component (A3) to the amount derived from the polymer matrix (A1) is 1:4 to 1:12; and / or, In the modified polymer matrix component (A), the molar ratio of the amount derived from component (A3) to the amount of polyisocyanate derived from component (A2) is 1:0.02 to 1:0.44; and / or, In the modified polymer matrix component (A), the molar ratio of the amount derived from the component (A3) to the amount derived from the latent curing agent of the component (A4) is 1:0.2 to 1:0.

4.

8. The polymer solid electrolyte according to any one of claims 1 to 7, characterized in that: The modification is carried out by one of the following methods: a. grafting the component (A3) polyol with the polymer base (A1) to obtain a graft, and then completing the formation of the three-dimensional network structure in the presence of the component (A2) polyisocyanate component and the component (A4) latent curing agent; b. Pre-reacting the polyol component (A3) with the polyisocyanate component (A2) to obtain a pre-reactant, and then reacting the pre-reactant with the polymer base (A1) in the presence of a latent curing agent component (A4) to form the three-dimensional network structure.

9. The solid electrolyte according to claim 8, characterized in that In the method a, the grafted product obtained by the grafting reaction is a comb-shaped grafted product with a polymer matrix molecular chain as a side chain; in the method b, the pre-reactant is coated on the polymer matrix or the pre-reactant is blended with the polymer matrix.

10. A lithium secondary battery, characterized in that: The lithium secondary battery comprises or uses the polymer solid electrolyte according to any one of claims 1 to 9. Preferably, the lithium secondary battery is an all-solid electrolyte lithium secondary battery.

Citation Information

Patent Citations

  • Bugphobic and icephobic compositions with fluid additives

    CN111655791A

  • Self-catalyzed gel polymer electrolyte, and preparation method and application thereof

    CN112436184A

  • Alkaline solid electrolyte based on waterborne polyurethane / ion conduction polymer composite foam and preparation method

    CN115612166A

  • Composition for ionically conductive polyelectrolyte and ionically conductive solid polyelectrolyte

    CN1293698A

  • Gel electrolyte

    JP1996064028A